2003
DOI: 10.1354/vp.40-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Classical Swine Fever Virus from Chronically Infected Pigs by In Situ Hybridization and Immunohistochemistry

Abstract: Abstract. Classical swine fever (CSF) virus (CSFV) nucleic acid and antigen were detected in 15 pigs with naturally occurring chronic CSF by in situ hybridization and immunohistochemistry. The most consistent and prominent microscopic lesions were perivascular mononuclear cell infiltration and gliosis in the central nervous system of pigs with chronic CSF. Positive cells typically exhibited a dark brown (in situ hybridization) or red (immunohistochemistry) reaction product in the cytoplasm without background s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Moreover, pigs inoculated with the virus carrying functional N pro in the triple mutant virus (vGPE - /N136D; T830A; V2475A; A2563V) showed a longer course of viremia than pigs infected with the parental END - triple mutant virus. Several reports suggested a role for the IRF3-degrading function of N pro in persistent infection in vascular endothelial cells [26], and in mononuclear cells and lymphocytes of lymph node cells, splenocytes and gut-associated lymphoid tissue cells [27,28]. Meyers et al suggested that N pro and E rns of bovine viral diarrhea virus are involved in establishing persistence after trans-placental infection in vivo [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pigs inoculated with the virus carrying functional N pro in the triple mutant virus (vGPE - /N136D; T830A; V2475A; A2563V) showed a longer course of viremia than pigs infected with the parental END - triple mutant virus. Several reports suggested a role for the IRF3-degrading function of N pro in persistent infection in vascular endothelial cells [26], and in mononuclear cells and lymphocytes of lymph node cells, splenocytes and gut-associated lymphoid tissue cells [27,28]. Meyers et al suggested that N pro and E rns of bovine viral diarrhea virus are involved in establishing persistence after trans-placental infection in vivo [29].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for PCV-2, classical swine fever virus (CSFV) and porcine reproductive and respiratory virus (PRRSV) was carried out using monoclonal mouse anti-CSFV antibody (WH303), monoclonal mouse anti-PCV-2 antibody and monoclonal mouse anti-PRRSV antibody (SDOW17) as described by Cheon and Chae (1999) and Choi and Chae (2003). In situ terminal deoxynucleotidyl transferase-mediated dUTP-biotin nicked end labelling (TUNEL) was also carried out to detect apoptotic markers as described by Choi and Chae (2002).…”
mentioning
confidence: 99%
“…Th e availability of reliable diagnostic tests is crucial for eff ective CSF control, and diff erent diagnostic laboratory test procedures for confi rmation of the viral antigen presence are available. Among them, immunohistochemistry proved to be a very reliable and suitable method for viral antigen detection in tissue samples, as well as for studying the pathogenesis of both natural and experimental CSFV infections (Belák et al, 2008;Polaček et al, 2007;2016;Sánchez-Cordon et al, 2003;Choi and Chae, 2003a;De las Mulas et al, 1997). Besides that, the importance of diagnostic IHC is further emphasized by the observation of Belák et al, (2008) where this test gave positive results long (even seven days) before the appearance of the fi rst clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…CSF viral distribution in diff erent tissues depends on strains of the virus (highly, moderately or low virulent strain), age of pigs, duration of infection, and susceptibility of the breed (Choi and Chae, 2003a). Th e immunohistochemical detection of CSFV antigen in tissues of both naturally and experimentally infected pigs over time is well , 1997).…”
Section: Discussionmentioning
confidence: 99%